Synthesis of crosslinked poly(methacrylic acid) shell/lipid core colloidal nanoparticles via L-in-Lm interfacial polymerization and their pH responsiveness - Nopparat Viriyakitpattana (2020)
© 2020 Elsevier B.V. In this present work, the synthesis of colloidal nanoparticles with crosslinked poly(methacrylic acid) (PMAA)-shell and lipid core via L-in-Lm interfacial polymerization was illustrated. The oil-in-water pre-emulsion of lipid (L) dispersed in an aqueous continuous phase containing monomer (Lm) was initially formed, and the polymerization took place at the oil/water interface. The oil phase contained sunflower oil (SF) as a model lipid and benzoyl peroxide (BPO) initiator, while an aqueous continuous phase consisted of methacrylic acid (MAA) as a model monomer, N,N’-methylenebis(acrylamide) (MBA) as cross-linker, and sodium dodecyl sulfate (SDS) as surfactant. After polymerization at elevated temperature, crosslinked PMAA was located on the surface of sunflower oil droplets as a shell layer, indicating that MAA monomer and MBA cross-linker were involved in the polymerization at the oil/water interface. The detailed investigation on the effects of polymerization parameters (e.g. polymerization temperature, initiator, monomer, surfactant, and cross-linker concentrations) was conducted. The physico-chemical properties, such as particle size, morphology, chemical composition, and pH-responsiveness were then determined. This synthetic route can provide PMAA-shell nanoparticles with accessibility and availability of carboxyl functional groups, and pH responsiveness that could be useful for various applications.